(untitled) (Quest Journal of Management and Social Sciences, 2024)
Background: Events are significant drivers of tourism and play a key role in the development and marketing of destinations. In Kathmandu Valley, the increasing trend of event organization has raised questions about visitor perceptions toward event management. However, no previous study has explored this topic in Nepal. Objective: The study aims to analyze visitor perceptions of event management in Kathmandu Valley, focusing on how affective engagement influences these perceptions and identifying areas for improvement. Method: An exploratory research design was adopted to uncover the realities of visitor perceptions. Quantitative data was collected from 343 respondents and analyzed using both descriptive and inferential statistics. Structural Equation Modeling (SEM) was employed to examine the relationships between variables. Result: The study found that affective engagement significantly impacts visitor perceptions. Attendees expect high-quality service from event companies and are likely to share their experiences on social media platforms like Facebook. Most respondents were between the ages of 21-30, indicating a strong youth interest in event attendance. The analysis revealed that one independent variable, affective engagement, had a significant effect on one hypothesis related to contingent factors, while another hypothesis was rejected. Conclusion: Event management companies in Kathmandu Valley should prioritize affective engagement, addressing attendees’ emotions and feelings. Enhancing internal management practices can lead to better service delivery, addressing common issues such as overcrowding, location, and security. Additionally, adopting modern technologies could further attract and satisfy attendees, improving overall event experiences. Paper Types: Research Paper Key words: Event management, Planned behavior, Affective engagement, SEM, Quality of the event JEL Classification: C38, D9, N95, N3